Precision Agriculture: Opportunities, Challenges and Future Perception in India - , Raj Kumar, Kuldeep Kumar, Deepak Singh, Kartik Tomar (Archives of Current Research International, 2025)
Agriculture plays a vital role in India's economy. 54.6 % of the total workforce is engaged in agriculture and allied sector activities (Census 2011) and accounts for 18.4 % of India's GVA at current prices during 2022-23. In recent times, precision farming has transformed traditional practices by leveraging cutting-edge technologies such as IoT, GPS, remote sensing, and data analytics to enhance efficiency and productivity in farming. Precision farming enhances agricultural efficiency by enabling accurate monitoring of soil moisture, weather conditions, seed quality, and yield forecasts. This approach tackles variations within and across fields, optimizing crop output while minimizing resource wastage. Precision agriculture offers transformative solutions to pressing issues like water scarcity, soil degradation, and stagnating farm incomes through site-specific crop management, precision irrigation, and real-time field monitoring. The government initiatives such as Digital India and PM-KISAN have begun promoting agri-tech integration; our findings suggest that accelerating PA adoption requires multi-stakeholder collaboration. Critical interventions include subsidized technology access, farmer education programs, and policy frameworks supporting scalable implementation. The study further highlights emerging opportunities in AI-driven decision support systems, drone-based surveillance, and low-cost sensor networks that could redefine India's agricultural future. These insights provide policymakers with actionable strategies to bridge the gap between PA's potential and practical implementation.